Efficient and Stable Thin‐Film Luminescent Solar Concentrators Enabled by Near‐Infrared Emission Perovskite Nanocrystals. Issue 20 (6th March 2020) - Wu, Jiajing; Tong, Jianyu; Gao, Yuan; Wang, Aifei; Zhang, Tao; Tan, Hairen; Nie, Shuming; Deng, Zhengtao
Abstract: A novel triphenylphosphine (TPP) treatment strategy was developed to prepare the near‐infrared emission CsPbI3 nanocrystal (NC)‐polymer composite thin‐film luminescent solar concentrators (LSCs) featuring high absolute photoluminescence quantum yield (PLQY), low reabsorption, and high stability. The PL emission of the LSCs is centered at about 700 nm with 99.4±0.4 % PLQY and narrow full width at half maximum (FWHM) of 75 meV (30 nm). Compared with LSCs prepared with classic CsPbI3 NCs, the stability of the LSCs after TPP treatments has been greatly improved, even after long‐term (30 days) immersion in water and strong mercury‐lamp irradiation (50 mW cm −2 ). Owing to the presence of lone‐pair electrons on the phosphorus atom, TPP is also used as a photoinitiator, with higher efficiency than other common photoinitiators. Large‐area (ca. 75 cm 2 ) infrared LSCs were achieved with a high optical conversion efficiency of 3.1 % at a geometric factor of 10. Abstract : TPP for LSCs : A triphenylphosphine (TPP) post‐treatment method was demonstrated for the preparation of highly stable, large‐area CsPbI3 nanocrystal–polymer composite thin‐film luminescent solar concentrators (LSCs). They have a high optical conversion efficiency and are highly emissive (absolute PLQY ca. 100 %).